HOW THE PAST SHAPES CURRENT STORIES: (EPI)GENETIC EPIDEMIOLOGICAL PROFILES OF METABOLIC SYNDROME IN BRAZILIAN MENNONITES (Arquivos do Mudi, 2023)
Mennonites present cc. 500 years genetic isolation and three bottleneck events that reduced their genetic diversity. In order to identify (epi)genetic markers for metabolic syndrome (MS), we used a modified version of the Brazilian National Health Survey to interview 762 Mennonites from three settlements, between 2016-2023. We compared 63 vs. 127 exomes (Illumina HiSeq) from Mennonites with/without metabolic syndrome (MS) and genotyped candidate variants in regulatory regions with mass spectrometry (iPLEX) and sequence-specific amplification (PCR-SSP). We also evaluated DNA methylation of the NR3C1 and FKBP5 genes in peripheral blood mononuclear cells (PBMCs) of up to 66 and 141 individuals with/without MS. MS prevalence was 35.8%, similar to Neobrazilians (34.8%), paradoxically followed by a three times lower prevalence of acute myocardial infarction (AMI). Among independent MS risk factors, we found lower maternal warmth in infancy (OR=1.59, P=0.019) and a higher susceptibility to AMI with the harshest migratory route to Brazil (OR=1.57, P=0.001). Thirty-nine variants of 34 genes were associated with MS (p